Mahir Menggambar 3D dan Mengoperasikan Printer 3D dalam Waktu Lima Hari - Fatra, Oka; Anam, Khoirul (Politeknik Penerbangan Indonesia Curug, 2021)
Community Service Program,”3-Dimensional Drawing and Operating 3D Printer in 5 Days for Intermediate Level”, arranged by Community Server is a part of responsibility to appreciate and to uphold the developing science and technology in 3-Dimensional drawing, both theoretically and practically that to be required for people. In addition to response of scholarship, it to be run for information sharing and combining some experiences with objects imagination by products. It had been packaged into two types of training model: Long Distance Training and Face-to-face Training. However, program was held by Long Distance Training refers to Corona Viruses. In this training, participants were required as partners consists of student, scholar and public that understanding about engineering science and capable in computer operating very well. This program had been running for 5 days. Theory learning through streaming video that used available platforms. Then, practical learning had been done by online and offline. Partners need to be developed their competency field by critical thinking with full of ideas, creative and collaborative in drawing of 3D object. Find many effective ways in 3D drawing of this program are important thing. So, every partner has to operate a 3D printer, in order to make 3D object become clearly visible into the real world.